Growth and physiological response of Yulu Hippophae rhamnoides to drought stress and its omics analysis - Haipeng Chen; Xiaolin Chen; Xiaogang Li; Xin Lin; Lihua Yue; Chunhai Liu; Yuling Li (Plant Signaling & Behavior)
Hippophae rhamnoides (H. rhamnoides) is the primary tree species known for its ecological and economic benefits in arid and semi-arid regions. Understanding the response of H. rhamnoides roots to drought stress is essential for promoting the development of varieties. One-year-old Yulu H. rhamnoides was utilized as the experimental material, and three water gradients were established: control (CK), moderate (T1) and severe (T2), over a period of 120 days. The phenotypic traits and physiological indies were assessed and analyzed, while the roots were subjected by RNA-Seq transcriptome and Tandem Mass Tags (TMT) proteome analysis. Drought stress significantly reduced the plant height, ground diameter, root biomass and superoxide dismutase activity; however, the main root length increased. In comparison with CK, a total of 5789 and 5594 differential genes, as well as 63 and 1012 differential proteins, were identified in T1 and T2, respectively. The combined analysis of transcriptome and proteome showed that the number of differentially expressed genes (DEGs) and differentially expressed proteins (DEPs) associated with T1, T2 and CK was 28 and 126, respectively, with 7 and 36 genes achieving effective KEGG annotation. In T1 and T2, the differential genes were significantly enriched in the plant hormone signal transduction pathway, but there was no significant enrichment in the protein expression profile. In T2, 38 plant hormone signal transduction function genes and 10 peroxisome related genes were identified. With the increase of drought stress, the combined expression of DEGs and DEPs increased. Yulu H. rhamnoides may allocate more resources toward CAT while simultaneously decreasing SOD and POD to mitigate the oxidative stress induced by drought. Furthermore, the molecular mechanisms underlying plant hormone signal transduction and peroxisome-related genes in the roots of H. rhamnoides were discussed in greater detail.